2001
DOI: 10.3327/jnst.38.1014
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear and Thermal Analyses of Supercritical-water-cooled Solid Breeder Blanket for Fusion DEMO Reactor.

Abstract: Within a design study of a fusion DEMO reactor aiming at demonstrating technologies of fusion power plant, supercritical water is applied as a coolant of solid breeder blanket to attain high thermal efficiency. The blanket has multi-layer composed of solid breeder pebbles (Li 2 O) and neutron multiplier pebbles (Be) which are radially separated by cooling panels. The first wall and the breeding region are cooled by supercritical water below and above the pseudocritical temperature, respectively. Temperature di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…We calculated the radioactivity for 2 years irradiation, which corresponds to the actual operation condition assumed in the DEMO blanket [10], with the following formula:…”
Section: Discussionmentioning
confidence: 99%
“…We calculated the radioactivity for 2 years irradiation, which corresponds to the actual operation condition assumed in the DEMO blanket [10], with the following formula:…”
Section: Discussionmentioning
confidence: 99%
“…The candidates of the breeder pebbles are Li 2 O or Li 2 TiO 3 , and Be or Be 12 Ti is applied as the neutron multiplier. The size of the pebbles will range from 0.2 mm to 2 mm in diameter [4]. The breeding layer is purged with Helium gas in order to recover Tritium.…”
Section: Design Of Fusion Power Plant "Demo"mentioning
confidence: 99%
“…Consequently, the tritium production might be changed by decrease of the atomic densities and the change of the neutron spectra due to the lithium burn-up. Numerous studies have been reported on the evaluation of TBR [1][2][3][4][5][6][7]. El-Guebaly et al reported the impact of tritium burn-up fraction on tritium start-up inventory [2].…”
Section: Introductionmentioning
confidence: 99%
“…DEMO reactors require the net tritium breeding ratio (TBR) of more than 1.05-1.1 [1,2] and a lot of design studies have been conducted to meet the requirement [1][2][3][4][5][6]. SlimCS is a conceptual design of a tokamak DEMO reactor being developed by JAEA [4].…”
Section: Introductionmentioning
confidence: 99%